Determinants of Emigrant Deposits in Cape Verde. (IMF Working Papers; Working Paper ;, 2006)
In the last decade Cape Verde has experienced a strong accumulation of emigrant deposits. These deposits have provided much needed foreign exchange to the country, adding support to the exchange rate peg. This paper studies the long-run determinants of emigrant deposits with respect to risk, wealth, and return variables, isolating speculative and altruistic motives underlying the accumulation of flows. The study suggests that the temporary character of recent emigration is responsible for the rise in the share of flows driven by altruism. Finally, the paper discusses policy implications in light of the empirical findings and the recent literature on this topic.